Jazz and Noir Film - Salamone, Frank A. (IJRDO - Journal of Social Science and Humanities Research, 2016)
Jazz became the music most associated with film noir. The key movie was The Wild One, starring Marlon Brando who personified the noir hero, or anti-hero. He was looking for trouble, any trouble. Great jazz figures were drawn to the noir form, and there was a noir style of music. West Coast trumpeter Shorty Rogers had 4 tunes in Leith Stevens great score. Great jazz stars Bud Shank, Jimmy Giuffre, Shelley Manne and the great Henry Mancini followed. The TV show Peter Gunn soon followed and kept great jazz musicians working. Jazz became the sound of the hardboiled detective and the noir film. Of course, the writings of Raymond Chandler, Dashiell Hammett, and Ernest Hemingway predated the films and TV shows. Since the 1930s, most orchestrations for movies are composed directly for the screen and, as we’ll see, cannot easily exist independent of the movie without much fleshing out. This is in contrast to a film using in its score the hit songs of an era, songs which existed independently, before the movie, and will exist independently after the movie is long gone even though it might be singularly associated with the film henceforth. Think of Roy Orbison’s classic hit, “Pretty Woman,” from the film Pretty Woman (1990). Or all the films with songs by Dean Martin, such as Moonstruck (1987), to establish both time and, often, place, such as Las Vegas or New York’s Little Italy. (Stuart Fischoff “The Evolution of Music in Film and its Psychological Impact on Audiences” p. 2)